Large extracellular vesicles derived from LPS-preconditioned cardiomyocytes alleviate myocarditis via mediating macrophage polarization and modulating p38 MAPK pathway - Jiang, Yanjie; You, Yingnan; Xie, Yaxue; Zhou, Shan; Ma, Mengjie; Han, Bo (Frontiers in Immunology, 2025)
IntroductionMyocarditis is an inflammatory injury to the myocardium characterized by disrupted intercellular communication, involving macrophages and cardiomyocytes as key players. However, the interactions between macrophages and cardiomyocytes during myocarditis remain inadequately explored. Emerging evidence indicated that extracellular vesicles (EVs) play a crucial role in intercellular communication. MethodsIn our study, LPS- or PBS-preconditioned cardiomyocytes derived large EVs (C-lEVLPS/C-lEVPBS) were isolated. qPCR, ROS and flow cytometry assays were employed to evaluate their impact on macrophages and in the in vivo experiments, C-lEVLPS was administered to mice with viral myocarditis. Cardiac function was assessed through echocardiography and cTnT levels, while inflammatory responses were analyzed via histopathological examination and cytokine profiling. Then mechanistic investigations were performed using integrated transcriptomic and proteomic profiling to characterize EV-mediated regulatory networks. Statistical analyses were performed using Student’s t-test or ANOVA, with significance set at p < 0.05.ResultsWe demonstrated C-lEVLPS exhibited anti-inflammatory effects on macrophages and alleviated cardiac inflammation and dysfunction in a mouse model of CVB3-induced myocarditis. Additionally, C-lEVLPS facilitated macrophage polarization toward the M2-like phenotype and inhibits M1 polarization, both in vitro and in vivo. Notably, compared to C-lEVPBS, C-lEVLPS was enriched in the phosphatase 2 scaffold subunit alpha protein (PP2AA), which can recruit other subunits to form the PP2A complex, ultimately leading to the dephosphorylates of p38. DiscussionThis study highlights the effect of C-lEVLPS in myocarditis and uncovers the potential mechanism that modulates macrophage polarization by delivering PP2AA from cardiomyocytes to macrophages and regulating the p38 MAPK pathway. These findings provide a promising therapeutic strategy for myocarditis.